2021
DOI: 10.1074/jbc.ra120.014479
|View full text |Cite
|
Sign up to set email alerts
|

The 89-kDa PARP1 cleavage fragment serves as a cytoplasmic PAR carrier to induce AIF-mediated apoptosis

Abstract: Poly(ADP-ribose) polymerase (PARP1) is a nuclear protein that is activated by binding to DNA lesions and catalyzes poly(ADP- ribosyl)ation of nuclear acceptor proteins, including PARP1 itself, to recruit DNA repair machinery to DNA lesions. When excessive DNA damage occurs, poly(ADP-ribose) (PAR) produced by PARP1 is translocated to the cytoplasm, changing the activity and localization of cytoplasmic proteins e.g. apoptosis-inducing factor (AIF), hexokinase and resulting in cell death. This cascade, termed par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 37 publications
1
75
0
Order By: Relevance
“…To further elucidate the mechanism underpinning the AIF(370-394) protective effect on the STS-treated SH-SY5Y cells, we also inspected the amounts of cleaved caspase-3 and PARP in both the cytosolic and nuclear extracts of cells treated and untreated with 10 µM STS. According to previous reports [ 5 , 34 ], in STS-treated cells, we detected a significant increase of activated caspase-3 and cleaved PARP, detected as the p24 subunit at ~24 kDa, in the cytosol and nucleus, respectively, compared to control cells ( Figure 4 C–F). The delivery of AIF(370-394) to STS-treated cells did not alter the levels of cleaved target proteins compared to cells treated with STS alone, indicating that the presence of the peptide did not influence the cell death mediated by caspase activation.…”
Section: Resultssupporting
confidence: 87%
“…To further elucidate the mechanism underpinning the AIF(370-394) protective effect on the STS-treated SH-SY5Y cells, we also inspected the amounts of cleaved caspase-3 and PARP in both the cytosolic and nuclear extracts of cells treated and untreated with 10 µM STS. According to previous reports [ 5 , 34 ], in STS-treated cells, we detected a significant increase of activated caspase-3 and cleaved PARP, detected as the p24 subunit at ~24 kDa, in the cytosol and nucleus, respectively, compared to control cells ( Figure 4 C–F). The delivery of AIF(370-394) to STS-treated cells did not alter the levels of cleaved target proteins compared to cells treated with STS alone, indicating that the presence of the peptide did not influence the cell death mediated by caspase activation.…”
Section: Resultssupporting
confidence: 87%
“…In turn, PARP-1 hyperactivation can initiate parthanatos—a programmed caspase-independent cell death ( Figure 2 ) [ 26 , 27 ]. PAR and PARylated proteins that are formed in large quantities migrate from a nucleus to cytoplasm and cause the release of apoptosis-inducing factor (AIF) from mitochondria [ 26 , 28 , 29 ]. Released AIF is transported to a nucleus due to a nuclear localization signal (NLS) and activates endonucleases, which cause DNA fragmentation followed by cell death.…”
Section: Relationship Of Parp-1 With Inflammatory and Metabolic Diseasesmentioning
confidence: 99%
“…In order to exclude apoptosis and cell death, we then verified through WB analysis, the expression of the pro-apoptotic marker, caspase3 (both precursor and cleaved versions of the enzyme) ( Widmann, 2007 ), and no differences were observed in treated vs. control cells ( Figures 6C,J ). Additionally, we performed WB for the full length PARP1 (116 kDa) and the large fragment (89 kDa) of PARP1 resulting from caspase cleavage ( Mashimo et al, 2021 ; Figures 6C,I ), as well as for the anti-apoptotic protein, BCL-2 ( Chipuk et al, 2010 ) (data not shown). In parallel, in Oli-Neu cells with AGC1 downregulation, the marker of mature oligodendrocytes CNPase ( Scherer et al, 1994 ) showed higher expression as compared to the control cells and was further induced by curcumin treatment ( Figures 6C,H ).…”
Section: Resultsmentioning
confidence: 99%